Direct radiative forcing due to aerosol properties at the Peruvian antarctic station and metropolitan Huancayo area - Angeles Suzao, Julio Miguel (2020)
We describe the results of the study of aerosol optical depth (AOD) and Direct Radiative Forcing (DRF) in Top Of Atmosphere (TOA), obtained from the measurement and monitoring campaign carried out during the XXI Antarctic Peruvian Expedition in the months of January and February 2013 and in the Metropolitan Huancayo Area in the months of June and July 2019. In the Scientific Peruvian Station at Antarctic “Machu Picchu” our used a SP02-L sun photometer, which is within the instrumental framework of the International Polar Year. This instrument has 4 channels: 412 nm, 500 nm, 675 nm and 862 nm, thus allowing direct radiation spectra measurements. And in the MHA we used the BF5 sensor. This instrument measured Direct, Diffuse and Global Radiation in low wavelength. The results calculated of AOD in polar latitudes varied between 0.0646 to 0.1061, in relation to AOD in MHA, presents the value maximum that is 0.58 (11 of June) and minimum that is 0.19 (12 June). The Angstrom coefficient was determined have values ranging from 0 to 0.07, these values also indicates the presence of big particles. Also to the MHA presents the mean value varied from 0 to 1.8, that indicated the presence the aerosols types biomass burning and industrial. Recorded optical properties used to estimate the direct aerosol radiative forcing (DARF) at the top of the atmosphere. The results indicates that on King George Island site the DARF is between [-2 4] W/m2; also, the direct aerosol radiative forcing in MHA is between [0 20] W/m2.